A model to promote the uptake of male circumcision as an HIV-preventive measure in high HIV and low male circumcision prevalence settings - Charles Maibvise; Thandisizwe R. Mavundla (AOSIS, 2019)
Background: Human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) remain the leading global burden of disease, especially in Southern Africa. As such, efforts to develop innovative preventive and curative measures continue to be a global priority. Of late, the World Health Organization recognised and recommended mass male circumcision (MC) as an adjunct HIV-preventive measure in 14 selected sub-Sahara African countries. However, despite efforts to promote the uptake of MC in these countries, the uptake remains significantly below set targets. Aim: The purpose of this article is to describe the process that was followed in developing, describing and evaluating a model to promote the uptake of MC as an HIV-preventive measure in high HIV and low MC settings. Setting: The model is designed for all settings of high HIV and low MC prevalence. Method: A theory-generative, qualitative, exploratory, descriptive and contextual research design was used. The process involved four distinct steps, namely concept analysis, description of relationship statements, and description and evaluation of the model using the criteria of clarity, simplicity, generality, accessibility and importance. Results: The central concept was identified as 'promote the uptake of MC', and three integral constituents were identified for the process, such as transforming men's mindsets about MC, facilitating accessibility and utilisation of MC services, and maintaining a supportive social system. These formed the basis for the model. Conclusion: The model provides a framework of reference for healthcare providers in promoting the uptake of MC as an HIV-preventive measure in high HIV and low MC settings.